Designer Profile 2012/2013 : vol. 1 industrial & exhibition design - Schmidt, Ulrich (Birkhauser Architecture, 2011)
Focuses on the design scene in Germany, Austria and Switzerland. This title enables designers from the fields of industrial, exhibition, graphic and multimedia design to present their ideas, concepts and successes. It is suitable for those who need speedy and targeted information on the many activities provided by potential designer partners